2007
DOI: 10.1590/s1516-80342007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Protocolo fonoaudiológico de avaliação do risco para disfagia (PARD)

Abstract: OBJETIVO: Os objetivos desse estudo foram: constituir um protocolo piloto de avaliação do risco para disfagia, visando auxiliar o fonoaudiólogo a identificar e interpretar as alterações na dinâmica da deglutição, caracterizar os sinais clínicos sugestivos de penetração laríngea ou aspiração laringo-traqueal, definir pontualmente a gravidade da disfagia e estabelecer condutas a partir dos resultados da avaliação. MÉTODOS: O Protocolo Fonoaudiológico de Avaliação do Risco para Disfagia foi elaborado com base na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0
88

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(227 citation statements)
references
References 19 publications
(80 reference statements)
0
112
0
88
Order By: Relevance
“…It is thus an independent sign of worse outcomes and increased mortality after stroke 12,13 . Recognizing this is extremely important for the performance of the speech therapy team in relation to stroke patients, in order to prevent and reduce hospital admissions and readmissions due to aspiration pneumonia, thereby aiming to stabilize the nutritional characteristics and improve the patients' quality of life 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…It is thus an independent sign of worse outcomes and increased mortality after stroke 12,13 . Recognizing this is extremely important for the performance of the speech therapy team in relation to stroke patients, in order to prevent and reduce hospital admissions and readmissions due to aspiration pneumonia, thereby aiming to stabilize the nutritional characteristics and improve the patients' quality of life 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to find a time of 4 seconds for liquid consistency 17 . However, the identification of a reference to the location of the pharyngeal phase firing is still an object of study, beyond the time of its phases.…”
Section: Discussionmentioning
confidence: 99%
“…For the degree of agreement among evaluators, the Landis and Koch classification 17 , being found that: <0.00 poor agreement; 0.00 to 0.19 poor agreement; 0.20 to 0.39 weak agreement; 0.40 to 0.59 moderate agreement; 0.60 to 0.79 substantial agreement; 0.80 to 1.00 almost perfect agreement.…”
Section: Methodsmentioning
confidence: 96%
“…They constitute a syndrome that can present alimentary refusal, fatigue and cough during the feeding, oral escape, nasal regurgitation, chokes, breathlessness, asphyxia, cyanosis and alteration of the vocal quality, beyond pulmonary problems and aspiration (5). They can also cause nutritional deficits and dehydration, resulting in weight loss, pneumonia and death (15).…”
Section: Discussionmentioning
confidence: 99%